Ask a New Question
Search
Solve for x log(base6)(x+3)−log(base6)(x−5)=2. I
Showing results
1
through
10
of 68,560.
prove:
1/log(base36)a = 2/log(base6)a i made a common base and then multiplied both sides with log(base6)a to get
1 answer
asked by
Anonymous
529 views
Solve for x log(base6)(x+3)−log(base6)(x−5)=2.
I tried to factor out the log(base6) and got (x+3)^x/(x-5)=2, but I don't know
4 answers
asked by
Ann
416 views
If 451 in base6 - P in base7 = 301 in base6, find d. value of P
5 answers
asked by
Ekingdeft
412 views
Multiply 235base6 and 43 base6
1 answer
asked by
Hassan
68 views
15513 base6 divided by43 base
23 answers
asked by
Hassan
70 views
log(base6)3600=5x
Whats the exact answer? show work please
1 answer
asked by
Orren
408 views
First: solve for k. Then, go back to the original equation c=k(d-3) and solve for c when d is ten.
Second: Area=k*s^2 Put in the
1 answer
asked by
SraJMcGinn
664 views
Put in the correct order
Solve exponentiation. Solve multiplication and division. Solve operations within parentheses Solve
1 answer
asked by
urmotherr
435 views
Combine like terms:
-3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 -
8 answers
asked by
Dawn
1,365 views
Solve the indicated variable:
1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32
1 answer
asked by
kitty kat
1,209 views
Pages
1
2
3
4
5
6
7
8
9
10